79.9k views
2 votes
Help pleaseeee I beg of you

Help pleaseeee I beg of you-example-1
User Fakemeta
by
4.6k points

1 Answer

7 votes

Answer:

The answer is option 2, 4 and 5.

Explanation:

Given that g(x) is equal to y. So image if you have to substitute x-value into the equation of y, you will get the y-value. In this question, it applies the same way. By looking at the graph :


when \: x = 0 \\ g(0) = 0


when \: x = 1 \\ g(1) = 1


when \: x = - 1 \\ g( - 1) = 1

User Helgetan
by
5.0k points